ANALYSIS OF THE POTENTIAL OF STREPTOCOCCUS SALIVARIUS ISOLATED FROM THE SALIVA AND TONGUE DORSUM TO INHIBIT THE GROWTH OF FUSOBACTERIUM NUCLEATUM - Nurfitri, Azzara; Joenoes, Hedijanti; Bachtiar, Boy M (International Journal of Applied Pharmaceutics, 2017)
Objective: Analyzing the potential of S. salivarius isolated from the saliva and tongue dorsum of adults to inhibit the growth of Fusobacterium nucleatum. Methods: Polymerase chain reaction, deferred antagonism test, and well-diffused agar test. Results: Inhibition of the growth F. nucleatum by S. salivarius isolated from the tongue dorsum (p>0.05). No inhibition to the growth of F. nucleatum by S. salivarius isolated from the saliva. No inhibition to the growth of F. nucleatum by the protein produced by S. salivarius. Conclusions: The growth of F. nucleatum was not inhibited by S. salivarius isolated from the saliva but by S. salivarius isolated from the dorsum of the tongue.